Rapid seismic risk assessment. (September 2017) - Kalman Šipoš, Tanja; Hadzima-Nyarko, Marijana
Abstract: This paper deals with seismic risk on the Croatian territory, especially since population growth in risk-prone areas increases the potential loss due to an earthquake. The net effects of such urbanization factors are examined through the use of simulation models that estimate building inventory under possible seismic hazard expressed with peak ground acceleration. A case study of seismic risk assessments is illustrated using Croatian cities to give an overview of the overall relative risk in Croatia as developing country using general parameters from Census data. Results of a prospective analysis indicate that, for the same seismic event, the overall risk is expected to increase due to growth of population in pre-code building inventory and populated areas and cities. This relative rapid assessment presented in this paper points out which cities need detailed analysis and enables city planners to incorporate seismic risk analysis into pre-disaster emergency and land-use planning to encourage risk-reduction strategies. The validation of proposed assessment was done on L'Aquila Province based on data after L'Aquila earthquake 2009. Results indicate prediction of realistic risk for the study area based on vulnerabilities of buildings and exposure of population with relative errors of 12% and 8% respectively.